Increasing the capacity of community resources through hospitality training - I Gusti Ayu Eka Suwintari; Putu Eka Wirawan; I Ketut Muliadiasa; Kadek Ayu Ekasani; Timotius Prastio (Community Empowerment, 2023)
Kenderan Village is a village located in Tegalalang District, Gianyar Regency. This village has several potentials that are an attraction for tourists to visit, such as Manuaba Waterfall and Griya Sakti Manuaba Temple at Tangkas Banjar, Telaga Waja Temple at Kepitu Banjar, Sarcophagus at Batulusu Subak Uma Lawas Kaja Temple, and many more. The purpose of this activity is to conduct pieces of training related to the fields of F&B Service, F&B Product, Housekeeping, and front office, with the main target being the local community involving village heads, tourism village managers, and the head of the Kenderan Village Pokdarwis. This activity is carried out through training and mentoring with workshop methods, guided practices, and comparative studies. The conclusion of these training activities was positive responses from the participants, the Head of Kenderan Village, and the Chair of the Pokdarwis of Kenderan Village and they also wanted this activity to be carried out continuously. In addition, there was an increase in the participants' understanding of their skills, this was seen from the number of those who passed competency certification as much as 81.8% in the areas of Food Service, Food Product, Housekeeping, and Front Office.